Public health significance of pronunciation of voices in pre-school children - Tasić Radica; Kekuš Divna; Stanisavljević Sanja; Antić Gordana (Association of Nurses Technicians and Midwives, 2019)
A survey conducted in the pre-school "Čika Jova Zmaj" in Belgrade between February and April 2016 in the pre-school age population showed significant representation of articulation disorders. In relation to the total number of children surveyed (427), the correct pronunciation was registered in 259 children (60.65%), while the dyslalia was registered with 168 children (39.34%). The reality that about 40% of preschool children today have a distortion of excuses, imposes the need to correct these disorders and highlights their public health significance from the perspective of potential problems in social integration and psychosocial development of these children. The results of our research on articulation disorders in pre-school children, depending on gender, were: in the pre-school age, 53% of speech disorders were recorded. Voice disorders of fricative, africat and lateral were present in over 80%, with prevalence from the group frikative. They dominated the distortion of the pronunciation of the following voices: L, Č, Š, Ž, S and Z, with the presence of distortion in over onethird of boys. In the population of pre-school age, speech disorders are represented by 46%. The voice disorders of fricative and africat are dominant. Distortion of pronunciation of voices CH, Š, S, C, Z and L, with prevalence of distortion, is singled out. The reality that articulation disorders are the most common speech disorders, imposes the need for systematic monitoring of articulation development at the earliest age. The first step towards the prevention of speech disorders is team work carried out in the framework of primary health care.